Trapped Behind the Wallpaper : A Thematic Study of Female Oppression in The Yellow Wallpaper - Natalia Br Surbakti; Enjelina Ambarita; Roselyn Sitompul; Nurhayati Purba (Pustaka Digital Indonesia, 2025)
This article explores the theme of oppression against women in Charlotte Perkins Gilman's short story The Yellow Wallpaper. Through thematic analysis, this study examines how the mental breakdown of the main character reflects rigid gender roles and patriarchal norms that dominated American society in the 19th century. The story follows a woman undergoing a ‘rest cure,’ a treatment method that emphasises isolation and prohibits intellectual activity, which only exacerbates her mental condition. Gilman not only criticises medical practices but also the oppressive social structures and marriages that silence women's voices. Symbolism, particularly the yellow wallpaper, plays a crucial role in depicting the protagonist's entrapment and despair. Her mental decline is understood not merely as an illness but as a symbolic form of resistance against oppressive norms. This finding suggests that The Yellow Wallpaper functions not only as a psychological study but also as a powerful feminist statement on the importance of autonomy, self-expression, and a gender-sensitive approach to mental health.